Salivary pH: A diagnostic biomarker - Sharmila Baliga; Sangeeta Muglikar; Rahul Kale (Wolters Kluwer Medknow Publications, 2013)
Objectives: Saliva contains a variety of host defense factors. It influences calculus formation and periodontal disease. Different studies have been done to find exact correlation of salivary biomarkers with periodontal disease. With a multitude of biomarkers and complexities in their determination, the salivary pH may be tried to be used as a quick chairside test. The aim of this study was to analyze the pH of saliva and determine its relevance to the severity of periodontal disease. Study Design: The study population consisted of 300 patients. They were divided into three groups of 100 patients each: Group A had clinically healthy gingiva, Group B who had generalized chronic gingivitis and Group C who had generalized chronic periodontitis. The randomized unstimulated saliva from each patient was collected and pH was tested. Data was analyzed statistically using analysis of variance technique. Results: The salivary pH was more alkaline for patients with generalized chronic gingivitis as compared with the control group (P = 0.001) whereas patients with generalized chronic periodontitis had more acidic pH as compared with the control group (P = 0.001). Conclusion: These results indicate a significant change in the pH depending on the severity of the periodontal condition. The salivary pH shows significant changes and thus relevance to the severity of periodontal disease. Salivary pH may thus be used as a quick chairside diagnostic biomarker.